Evaluation of regional climate models and future wind characteristics in the Black Sea - Islek, Fulya; Yuksel, Yalcin; Sahin, Cihan (WILEY, 2022)
The main objective of the present study is to provide a comprehensive image of the expected wind patterns along the 21st century in the Black Sea using the wind fields simulated by Regional Climate Model (RCM), namely Rossby Centre regional atmospheric model (version RCA4). Long-term averages, long-term variability, and long-term trends in wind characteristics over the Black Sea are evaluated in two future time slices (near future 2021-2060 and middle future 2061-2100) under the two climate scenarios (RCP4.5 and 8.5). Detailed analysis of wind (annual mean and 99th percentile wind speeds) and storm characteristics (number and duration of storms) are conducted for three different locations selected on the same meridional section to assess the variability on the wind characteristics from west to east. Spatiotemporal variability on the wind characteristics indicates that the eastern Black Sea will be characterized by lower mean wind speed, stronger 99th percentile wind speed, and higher variability. Considering the global indicators of climate change (e.g., increasing frequency and intensity of extreme events), the eastern Black Sea, characterized by complex atmospheric circulation due to surrounding mountains, is more likely to be subjected to the impacts of climate change as the occurrence of extreme wind speeds in future periods is more prominent in this region. In the future periods, the 100-year return period wind speeds increase approximately 7% and 27% in the western and eastern Black Sea, respectively, compared to the historical period. The strong and relatively stable winds with low variability in the western Black Sea indicate a reliable, persistent, and sustainable wind energy potential in this region in the future.
Keywords: Black Sea; climate change; EURO-CORDEX; regional climate models; wind characteristics; PROJECTIONS; SATELLITE; VELOCITY; IMPACT; SPEED; Meteorology & Atmospheric Sciences